Distributions of Pu isotopes in seawater and bottom sediments in the coast of the Japanese archipelago before and soon after the Fukushima Dai-ichi Nuclear Power Station accident. (April 2015) - Oikawa, Shinji; Watabe, Teruhisa; Takata, Hyoe
Abstract: A radioactivity measurement survey was carried out from 24 April 2008 to 3 June 2011 to determine the levels of plutonium isotopes and 240 Pu/ 239 Pu atom ratios in the marine environments off the sites of commercial nuclear power stations around the Japanese islands; the sampling period extended to two months after the Fukushima Dai-ichi Nuclear Power Station accident. In our previous study (Oikawa et al., 2015 ), data on Pu isotopes and 241 Am in sediments have already been reported. In this study, we report those on Pu isotopes in seawater as well as sediments, and the characteristics of sediments in addition (e.g., ignition loss and biogenic opals). Concentrations of 239+240 Pu in seawater and bottom sediments remained nearly constant at all sampling locations during the survey period. In addition, no regional differences were observed in the 239+240 Pu concentrations in surface waters. Higher 239+240 Pu concentrations were found in bottom waters at deeper sampling locations, but the 240 Pu/ 239 Pu atom ratios were nearly constant regardless of the water depth. Higher 239+240 Pu concentrations were also found in bottom sediments at deeper sampling locations, but vice versa for 240 Pu/ 239 Pu atom ratios as reported in the previous report. The sediments samples from deeper locations showed the higher percentage of ignition loss as well as the higher content of biogenic opal. There was likely to be some driving force participating in the transfer of Pu isotopes associated with biogenic substances to the deeper seabed. The present survey showed that the accident at the Fukushima Dai-ichi Nuclear Power Station did not contribute much to the inventory of Pu isotopes in the adjacent sea area. Highlights: Pu concentration off the Japan coast before and after FDNPS accident was measured. No regional differences were observed in 239+240 Pu concentrations in surface waters. 240 Pu/ 239 Pu atom ratios were also nearly identical in seawaters. There were no significant differences in the ratio in sediments. FDNPS accident did not contribute to the inventory of Pu isotopes in the adjacent seas.